Answered

At Westonci.ca, we make it easy for you to get the answers you need from a community of knowledgeable individuals. Join our Q&A platform to connect with experts dedicated to providing precise answers to your questions in different areas. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.

Simplify the polynomial.

1. 4a²b + 5 - 6a³b - 3a²b + 2a³b


Sagot :

Lilith
[tex]1.\\ \\ 4a^2b + 5 - 6a^3b - 3a^2b + 2a^3b = \\ \\ = - 6a^3b + 2a^3b +4a^2b - 3a^2b+ 5=\\ \\= - 4a^3b + a^2b + 5[/tex]


4a²b + 5 - 6a³b - 3a²b + 2a³b

We first simplify similar expressions,

4a²b - 3a²b + 5 -6a³b + 2a³b

= a²b + 5 - 4a³b